Identification of GSK3 Family Genes in Pear and Their Expression Analysis Under Drought Stress - Kairan Hu; Ziyi Zhang; Guoliang Li; Shuliang Zhao; Yali Zhang; Qingjiang Wang; Fuhou Cheng (Life)
Members of the glycogen synthase kinase 3 (GSK3) family in plants, as a class of serine/threonine protein kinases, have been demonstrated to play crucial roles in a wide range of biological processes and environmental stresses. However, the GSK3 gene family has not been analyzed in pears. In this study, 12 GSK3 gene family members were identified in the Pyrus bretschneideri genome. These genes were located on 10 chromosomes and phylogenetically classified into four subfamilies. All 12 PbGSK3 proteins possessed highly conserved domains. The results demonstrated the structural characteristics of all 12 PbGSK3s and the evolutionary processes of their putative proteins. The presence of several cis-acting elements in the promoter region of the PbGSK3s associated with hormonal and stress responses suggested that the PbGSK3s might be involved in the growth and development of pears and in stress response. The expression profiles of PbGSK3s under drought stress were also analyzed. When the pears were subjected to drought stress for different durations, the expression patterns of 12 PbGSK3s exhibited variations. The findings would provide a scientific foundation for further exploration of the potential functions of the GSK3 genes in pears.